(untitled) (Revista Internacional de Formação de Professores, 2017)
The origin of this exploratory study is the inverse trend between genders observed in the entry marks on the Teacher Training Programme and the final marks. An analysis of possible reasons for this inversion, based on trainee teachers’ accounts, is made concerning this curricular unit. The study was conducted using a questionnaire with four groups of questions, applied to 106 trainee teachers attending a Master’s in Physical Education Teacher Training. A quantitative, descriptive statistical methodology treating closed questions was conciliated with a qualitative methodology of content analysis of open and semi-open questions. A process of categorization by semantic criterion was used, with previously defined dimensions but without categories formed from the outset. A discussion procedure between peers served for the validation of those categories and the codification of the respective segments used. The results do not support nor justify the skew in the final marks for either gender nor do they justify the higher initial marks of the males that triggered this study. Thus, the need to investigate issues related to the student’s gender versus the assessor’s gender in evaluation further, as well as the necessity of validating the questionnaire, has become evident.